CSF-resident CD4+ T-cells display a distinct gene expression profile with relevance to immune surveillance and multiple sclerosis. Issue 3 (13th July 2021) - Hrastelj, James; Andrews, Robert; Loveless, Samantha; Morgan, Joanne; Bishop, Stefan Mark; Bray, Nicholas J; Williams, Nigel M; Robertson, Neil P
Abstract: The CNS has traditionally been considered an immune privileged site, but is now understood to have a system of immune surveillance, predominantly involving CD4 + T-cells. Identifying functional differences between CNS and blood CD4 + T-cells, therefore, have relevance to CNS immune surveillance as well as to neurological conditions, such as multiple sclerosis, in which CD4 + T-cells play a central role. Here, CD4 + T-cells were purified from CSF and blood from 21 patients with newly diagnosed treatment-naïve multiple sclerosis and 20 individuals with non-inflammatory disorders using fluorescence-activated cell sorting, and their transcriptomes were profiled by RNA sequencing. Paired comparisons between CD4 + T-cells from CSF and blood identified 5156 differentially expressed genes in controls and 4263 differentially expressed in multiple sclerosis patients at false discovery rate <5%. Differential expression analysis of CD4 + T-cells collected from the CSF highlighted genes involved in migration, activation, cholesterol biosynthesis and signalling, including those with known relevance to multiple sclerosis pathogenesis and treatment. Expression of markers of CD4 + T-cell subtypes suggested an increased proportion of Th1 and Th17 cells in CSF. Gene ontology terms significant only in multiple sclerosis were predominantly those involved in cellular proliferation. A two-way comparison of CSF versus blood CD4 + T-cells in multiple sclerosis compared with non-inflammatory disorder controls identified four significant genes at false discovery rate <5% ( CYP51A1, LRRD1, YES1 and PASK ), further implicating cholesterol biosynthesis and migration mechanisms. Analysis of CSF CD4 + T-cells in an extended cohort of multiple sclerosis cases (total N = 41) compared with non-inflammatory disorder controls (total N = 38) identified 140 differentially expressed genes at false discovery rate < 5%, many of which have known relevance to multiple sclerosis, including XBP1, BHLHE40, CD40LG, DPP4 and ITGB1 . This study provides the largest transcriptomic analysis of purified cell subpopulations in CSF to date and has relevance for the understanding of CNS immune surveillance, as well as multiple sclerosis pathogenesis and treatment discovery. Abstract : Hrastelj et al. report the largest transcriptomic comparison of CSF and blood CD4 + T-cells to date. The study identifies thousands of significant genes, implicating cellular migration and cholesterol metabolism, as well as Th1, Th17 and effector memory function in immune surveillance of the CNS in multiple sclerosis and controls. Graphical Abstract: